TiH2 microporous replication pseudo-elastic NiTi alloy by metal injection moulding / Ros Atikah Abdul Kadir - Abdul Kadir, Ros Atikah (2017)
Numerous studies have been done on implementing MIM to manufacture products for biomedical applications by employing NiTi alloy as a main subject. NiTi alloy is renowned materials with their good mechanical properties and pseudo-elastic behaviour. This study aims to study the effect of TiH2 on thermal and behaviour of the feedstock, impurity contents and reversible phase transformation temperature (PTT) of NiTi alloy and to determine the mechanical properties of the samples. Two different compositions (50 at% Ni and 50.4 at% Ni) with three different powder loadings (65.5 vol%, 67.5 vol% and 69.5 vol%) were used in this research. The powder mixtures were blended in ball milling and mixed with two different binders known as palm stearin (PS) and polyethylene (PE) using brabender mixer. The flow behaviour of the feedstock was determined using rheology test. It shows that all feedstocks exhibit pseudoplastic behaviour which is suitable for MIM. The samples were injected into staple shape and tensile shape; then went through solvent debinding at temperature 60°C to remove palm stearin, thermal debinding at temperature 500°C in argon environment and finally sintered at temperature 1100°C. The characterisation of thermal, physical and mechanical properties and microstructure of the as-sintered samples was performed. The samples were tested for constituent phase morphologies, pore analysis, phase transformation temperatures and load-unload tensile test. During the sintering process, NiTi (B2) and other secondary phases (NiTi2, Ni3Ti and Ni4Ti3) with interconnected pores were formed due to the formation of Kirkendall effects. The use of TiH2 was able to reduce the formation of intermetallic phases with the help of calcium hydride (CaH2) as a reducing agent during the sintering process. It is possible that NiTi can be sintered using argon environment despite high vacuum condition; thus reducing the production cost of fabricating final samples. The pore size values for all samples were within the range of 20-100µm which was suitable for implant with minimum requirement of 50µm. Besides that, the carbon and oxygen content decreased significantly at highest powder loading because of the better inter-diffusion due to the existence of transient liquid formation which lead to the phase homogenization. The austenite temperature for the samples was within the range of 21°C to 28°C which proved the existence of pseudo-elastic behaviour and shape memory effect that correlated with the load-unload tensile test where the elastic deformation of all samples was around 2% to 6% strain. All related data demonstrated that NiTi was suitable as biomedical implants. Furthermore, the Young’s Modulus value calculated from stress-strain curves was around 1.1 to 1.4 GPa which was very close to the cancellous bone (< 3 GPa); thus, it made these alloys suitable for bone implant.